2015
DOI: 10.3897/compcytogen.v9i3.5263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic studies in the ladybird beetle Henosepilachna argus Geoffroy, 1762 (Coleoptera, Coccinellidae, Epilachninae)

Abstract: The ladybird Henosepilachna argus Geoffroy, 1762 has been cytogenetically studied. In addition we have conducted a review of chromosome numbers and the chromosomal system of sex determination available in the literature in species belonging to the genus Henosepilachna and in its closely related genus Epilachna. Chromosome number of Henosepilachna argus was 2n=18, including the sex chromosome pair, a common diploid chromosome number within the tribe Epilachnini. The study of prophase I meiotic chromosomes showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Telomeric TTAGG probe generation and FISH assays were carried out following Lorite et al (2002) and Mora et al (2015). Telomeric probes were generated by PCR using the primers (TTAGG) 6 and (TAACC) 6 , following a similar procedure as described by IJdo et al (1991).…”
Section: Methodsmentioning
confidence: 99%
“…Telomeric TTAGG probe generation and FISH assays were carried out following Lorite et al (2002) and Mora et al (2015). Telomeric probes were generated by PCR using the primers (TTAGG) 6 and (TAACC) 6 , following a similar procedure as described by IJdo et al (1991).…”
Section: Methodsmentioning
confidence: 99%
“…A recent revision of the tribe Epilachnini placed the ladybird beetle Henosepilachna argus into the genus Chnootriba [33]. The chromosome number in this species is 2n = 18 with an Xy parachute sex chromosome system [12]. The Y chromosome was minute and for this reason it is often written with a lowercase letter.…”
Section: Resultsmentioning
confidence: 99%
“…C-banding of C. argus chromosomes showed the presence of large heterochromatic pericentromeric regions on all chromosomes, including the sexual pair. Staining with DAPI showed that the DNA located on these regions was A+T rich [12]. Since satDNA is the main component of the heterochromatin, another or other satDNA families must be present on those pericentromeric regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent publications have shown that the number and chromosomal locations of the major rDNA multigene families are useful for the study of karyotype evolution in other insect groups (e.g. Grzywacz et al 2011: Orthoptera; Gokhman et al 2014: Hymenoptera; Vershinina et al 2015: Lepidoptera; Lachowska-Cierlik et al 2015: Mantophasmatodea; Mora et al 2015: Coleoptera).…”
Section: Discussionmentioning
confidence: 99%